Senator Ralph Yarborough, Democrat of Texas, who was present in the motorcade when the President was shot. He is here being interviewed on the day after that event on C.B.S
Senator Ralph Yarborough, Democrat of Texas, who was present in the motorcade when the President was shot. He is here being interviewed on the day after that event on C.B.S.